The Effect of Audit Information Systems on Audit Quality Control - Fitriani, Novi; Sania, Flora; Sagala, Mohamad Hafidz; Wardhani , Neng Sri (CV Raskha Media Group, 2025)
The increasing complexity of organizational processes has intensified the need for effective audit quality control to ensure reliable and accountable audit outcomes. Audit Information Systems (AIS) have emerged as a critical tool in supporting internal audit activities, particularly in managing audit findings and enhancing audit quality control. However, empirical evidence regarding the effectiveness of audit information systems in improving audit quality control remains limited, especially in the context of internal audits. This study aims to examine the effect of audit information systems on audit quality control, with particular attention to the management of audit findings. The research adopts a quantitative approach using data collected from internal auditors through structured questionnaires. Statistical analysis is employed to assess the relationship between audit information systems, audit findings management, and audit quality control. The results indicate that audit information systems have a significant positive effect on audit quality control by improving data accuracy, consistency, transparency, and timeliness of audit processes. Furthermore, effective management of audit findings through information systems contributes to enhanced audit accountability and compliance with audit standards. These findings highlight the strategic role of audit information systems in strengthening internal audit functions and supporting organizational governance. The study contributes to the literature on audit information systems and provides practical implications for audit institutions seeking to improve audit quality control through digital transformation.